Dampak Pandemi COVID-19 dan Kebijakan Work From Home Terhadap Masyarakat Miskin dan Perempuan di Perdesaan - Lutfi Apreliana Megasari; Siti Mas'udah; Priyono Tri Febrianto (Society, 2021)
The COVID-19 outbreak has brought multiple profound effects on the economic sector worldwide. This study aims to determine the socio-economic impact caused by the COVID-19. Considering Indonesian lower-classes, this study used a quantitative method with a descriptive approach and collected 274 respondents. Data were obtained from questionnaire interviews with poor women in rural East Java. The data source was selected using a random sampling technique. Literature studies were carried out to collect data related to research. The results show that the pandemic in Indonesia has caused a tremendous impact on the socio-economic sector of society and women from the lower classes in rural areas. They suffer from huge losses ranging from reduced income to loss of work. This study also highlights the Work From Home (WFH) policy, which cannot be implemented on the lower classes because many of them are laid off, and some employees who continue to work are at risk of disease exposure. Likewise, the COVID-19 pandemic and Work From Home (WFH) policy evoke several problems for women. The household responsibility of women is proven to increase during the pandemic. The women who do WFH seem to be preoccupied in two roles, first, as a worker, second, as a housewife who assists the household. Specifically, it means women are required to do domestic and public work. Therefore, gender awareness is needed to minimize women’s disadvantages in this case.